(untitled) (Revista de Educação Pública, 2013)
Revista de Educação Pública - v. 22, n. 51 (set./dez. 2013) Cuiabá,EdUFMT, 2013, 240 p.Anual: 1992-1993. Semestral: 1994-2005. Quadrimestral: 2006-ISSN Eletrônico 2238-2097ISSN Impresso 0104-5962